Structural basis of Iridoid synthase mediated cyclization of 10-oxogeranial - Sandholu, Anandsukeerthi; H. V. Thulasiram; Sengupta, Jayati; Kulkarni, Kiran (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Cryo-EM; iridoid synthase; Single Particle reconstruction

Structural studies on an atypical Rho GTPase RhoH - Motiwala, Zenia; Kulkarni, Kiran (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: lymphoma; RhoH; TCR signalling

Structural studies on 10-hydroxygeraniol dehydrogenase: a novel linear substrate-specific dehydrogenase from Catharanthus roseus - Sandholu, Anand S.; Mujawar, Sharmila P.; Ramakrishnan, Krithika; Thulasiram, Hirekodathakallu V.; Kulkarni, Kiran (Proteins-Structure Function and Bioinformatics, 2020)
Conversion of 10-hydroxygeraniol to 10-oxogeranial is a crucial step in iridoid biosynthesis. This reaction is catalyzed by a zinc-dependent alcohol dehydrogenase, 10-hydroxygeraniol dehydrogenase, belonging to the family of medium-chain dehydrogenase/reductase (MDR). Here, we report the crystal structures of a novel 10-hydroxygeraniol dehydrogenase from Catharanthus roseus in its apo and nicotinamide adenine dinucleotide phosphate (NADP(+)) bound forms. Structural analysis and docking studies reveal how subtle conformational differences of loops L1, L2, L3, and helix alpha 9' at the orifice of the catalytic site confer differential activity of the enzyme toward various substrates, by modulating the binding pocket shape and volume. The present study, first of its kind, provides insights into the structural basis of substrate specificity of MDRs specific to linear substrates. Furthermore, comparison of apo and NADP(+) bound structures suggests that the enzyme adopts open and closed states to facilitate cofactor binding.
Keywords: 10-hydroxygeraniol dehydrogenase; iridoid biosynthesis; medium-chain dehydrogenase; monoterpene indole alkaloids; reductase; X-ray crystallography

Substrate induced dynamical remodeling of the binding pocket generates GTPase specificity in DOCK family of guanine nucleotide exchange factors - Roy, Debopriya; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2022)
Dedicator of cytokinesis (DOCK) family of guanine nucleotide exchange factors (GEFs) activate two members of Rho family GTPases, Rac1/Cdc42, to exert diverse cellular processes, including cell migration. As DOCK GEFs have been critically implicated in tumour cell migration, understanding their function and specificity is imperative for designing anti-metastatic drugs. Based on their GTPase specificity they have been classified as Rac, Cdc42 and dual specific GEFs. Despite extensive structural studies, the factors that determine GTPase specificity of DOCK GEFs have remained elusive. Here, we show that subtle dynamical coupling between GEF and GTPase structures modulate the binding interface to generate mutual spec-ificity. To cluster the dynamically coupled residues in GEF-GTPase complexes a novel intra-residue backbone-torsion-angles based mutual information (TMI) technique was employed. TMI was calcu-lated from 4500 trajectories obtained from a total of 4.5ms molecular dynamics simulations performed on members of all the three clades of DOCK GEFs. The obtained clusters suggest a specificity generation mechanism that involves optimization of the binding pocket for the crucial divergent residue at the 56th position of Rac/Cdc42 (FCdc42/WRac1). These clusters encompass five residues from the structural segment lobe C -a10 helix of the DOCK proteins and functional SWI region of GTPase, which induce orchestrated structural modulations to generate the specificity. Even the conserved residues from SWI region are seen to augment the specificity defining dynamical rearrangements. Furthermore, the pro-posed dynamical GTPase-DOCK GEF specificity model was verified using mutagenesis studies on Rac1 and dual GTPase specific Dock2 and Dock6, respectively. Thus the current study provides the generic substrate specificity determinants of DOCK GEFs, which are not apparent from the conventional struc-tural analysis.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Dedicator of cytokinesis; GTPase specificity; Guanine exchange factors; Molecular dynamics simulations; Mutual information; Rho GTPases

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography